2016
DOI: 10.1136/bmjopen-2015-010806
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Ageing Through Internet Counselling in the Elderly: the HATICE randomised controlled trial for the prevention of cardiovascular disease and cognitive impairment

Abstract: IntroductionCardiovascular disease and dementia share a number of risk factors including hypertension, hypercholesterolaemia, smoking, obesity, diabetes and physical inactivity. The rise of eHealth has led to increasing opportunities for large-scale delivery of prevention programmes encouraging self-management. The aim of this study is to investigate whether a multidomain intervention to optimise self-management of cardiovascular risk factors in older individuals, delivered through an coach-supported interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(113 citation statements)
references
References 53 publications
1
108
0
4
Order By: Relevance
“…There is limited evidence on the efficacy of interventions designed to simultaneously address multiple risk behaviours in a primary care setting. It seems that multifactorial interventions produce small changes in lifestyle and if maintained over time, they could lead to a significant improvement in cardiovascular risk, quality of life and cognitive decline (Goldstein et al., ; Richard et al., ; Sweet & Fortier, ). However, it is still not clear whether it is more effective to use group or individual interventions in simultaneously addressing various risk factors (Bayley et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…There is limited evidence on the efficacy of interventions designed to simultaneously address multiple risk behaviours in a primary care setting. It seems that multifactorial interventions produce small changes in lifestyle and if maintained over time, they could lead to a significant improvement in cardiovascular risk, quality of life and cognitive decline (Goldstein et al., ; Richard et al., ; Sweet & Fortier, ). However, it is still not clear whether it is more effective to use group or individual interventions in simultaneously addressing various risk factors (Bayley et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The SMArTVIEW trial (Self‐MAnagemenT‐VIsion for patient EmpoWerment), currently ongoing in the United Kingdom, will analyze whether Bluetooth enabled monitoring devices and mHealth‐delivered educational materials will optimize the ability of older adults following cardiac surgery to recognize when they require medical attention with hopes of improving postoperative outcomes . Also ongoing, the HATICE trial (Healthy Ageing Through Internet Counselling in the Elderly) will provide older adults at high risk for CVD with an interactive internet platform with educational materials and remote support by a coach with the goal of optimizing risk factors …”
Section: Applications Of Mhealth In Older Adults: An Overviewmentioning
confidence: 99%
“…These include several drugs under development to modify Alzheimer's disease (AD) by targeting amyloid, and multidomain interventions targeting modifiable risk factors by means of lifestyle and cardiovascular disease management (Winblad et al, 2016). The latter has been evaluated by various trials (Ngandu et al, 2015;Richard et al, 2016;Vellas et al, 2014) on the primary prevention of dementia before the first dementia-related symptoms occur. They include the Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER) study, which found that people aged 60-77 who were at risk for dementia, with normal or slightly diminished cognition, and received a multidomain intervention (consisting of diet, exercise, cognitive training and vascular risk monitoring), showed an 0.20 improvement in the Z-score of a neuropsychological test battery after two years, which was more than the control group (Ngandu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%